Answer:
Part A:The function f(x) has a greater slope than function g(x).Part B:The function f(x) has a greater y-intercept than function g(x).Step-by-step explanation:
[tex]\text{The slope-intercept form of an equation of a line:}\\\\y=mx+b\\\\m-slope\\b-y-intercept\to(0,\ b)\\\\\text{The formula of a slope:}\\\\m=\dfrac{y_2-y_1}{x_2-x_1}\\\\=============================[/tex]
[tex]f(x):\\\\given:\ (-1,\ -5),\ (0,\ -1),\ (1,\ 3)\\\\m=\dfrac{3-(-5)}{1-(-1)}=\dfrac{8}{2}=4\\\\(0,\ -1)\to b=-1\\\\f(x)=4x-1\\\\---------------------------\\\\g(x)=2x-7\to m=2,\ b=-7[/tex]
Answer:
Part A: The slope of F(x) is greater than the slope of g(x)
Part B: The Y-intercept of f(x) is greater than that of g(x)
Step-by-step explanation:
To calculate the slope on f(x) we just have to take two points from the table and use the formula for slope:
[tex]m=\frac{y^{2} -y^{1} }{x^{2}- x^{1} }[/tex]
Now the points to use will be:
P1:(0,-1)
P2:(1,3)
Now we just put this values into the formula:
[tex]m=\frac{y^{2} -y^{1} }{x^{2}- x^{1} }[/tex]
[tex]m=\frac{3-(-1) }{1- (0)} }[/tex]
[tex]m=\frac{4}{1}\\ m=4[/tex]
Now to know the slope of g(x) we just have to remember that in the function form y=mx+c the "m" represents the slope, so if g(x)=2x-7 the slope would be "2".
Now we know that f(x) has a greater slope.
To know the greater Y intercept we just take the point in the table where x is "0" since it´s where the Y intercepts with the Y axis, and in f(x) that point is (0,-1), now in g(x) we just evaluate the function to x=0.
[tex]g(x)=2x-7\\g(x)=2(0)-7\\g(x)=-7[/tex]
The Y intercept in g(x) would be in (0,-7), since -1 is greater than -7, we can say that f(x) has the greatest Y-intercept.
PLS HELP ME!!!the base length of a triangle is 12 ft and the height is 6 ft. what is the area of the triangle.
a. 10 sq. ft
b. 12 sq. ft
c. 18 sq. ft
d. 36 sq. ft
Answer:
d. 36 sq. ft
Step-by-step explanation:
The area of a triangle is given by
A = 1/2 bh where b is the base and h is the height
A = 1/2 (12) * 6
A = 36 ft^2
what is the nth term of 2,5,8,11,14
Answer:
f(n) = 2 + 3(n-1)
Step-by-step explanation:
Answer:
f(n) = 2 + 3(n-1)
Step-by-step explanation:
solve for d -4c+3d=8e
Hey there! :)
-4c + 3d = 8e ; solve for d.
In order to solve for d, you must isolate it (get it onto its own side). So, let's start off by adding 4c to both sides.
-4c + (-4c) + 3d = 8e + (-4c)
Simplify.
3d = 8e - 4c
Then, divide both sides by 3.
3d ÷ 3 = (8e - 4c) ÷ 3
Simplify.
d = 8/3e - 4/3c
Therefore, [tex]d = \frac{8}{3} e -\frac{4}{3} c[/tex]
What is the difference of the rational expressions below?
X+5/x^2-2/5x
Answer:
[tex]\large\boxed{\dfrac{x+5}{x^2}-\dfrac{2}{5x}=\dfrac{3x+25}{5x^2}}[/tex]
Step-by-step explanation:
[tex]\dfrac{x+5}{x^2}-\dfrac{2}{5x}=\dfrac{5(x+5)}{5x^2}-\dfrac{2x}{5x^2}\qquad\text{use the distributive property}\\\\=\dfrac{5x+25}{5x^2}-\dfrac{2x}{5x^2}=\dfrac{5x+25-2x}{5x^2}=\dfrac{3x+25}{5x^2}[/tex]
The difference between the rational expressions below will be,[tex]\frac{3x+25}{5x^2}[/tex]
What is an arithmetic operation?Arithmetic is an area of mathematics involving the study of numbers and the different operations that can be performed on them.
The difference in the rational expression is found as;
[tex]=\frac{x+5}{x^2} -\frac{2}{5x} \\\\=\frac{5(x+5)}{x^2} - \frac{2x}{5x^2} \\\\\ = \frac{5x+25}{5x^2} -\frac{2x}{5x^2 }\\\\\ = \frac{5x+25-2x}{5x^2} \\\\ = \frac{3x+25}{5x^2}[/tex]
The difference between the rational expressions below will be,[tex]\frac{3x+25}{5x^2}[/tex].
To learn more about the arithmetic operation, refer to the link;https://brainly.com/question/25834626
#SPJ2
Which equation can be solved using the expression -3 plus or minus the square root of (3)^2+4(10)(2)/2(10) for x?
A. 10x^2=3x+2
B. 2=3x+10x^2
C. 3x=10x^2-2
D. 10x^2+2=-3x
Answer: B. 2=3x+10x^2
Step-by-step explanation:
The expression means the quadratic function equation.
B = 10x^2 + 3x -2 = 0
the equation is [-b ±√(b^2 -4ac)]/2a
b should be +3 to become -3 when it is plugged into the equation, and 'a' should be 10, and c should be -2.
Answer:B
Step-by-step explanation:
Ye you know me keep it a buck like 123 ye 2022 baby
Please help explain to me please I want to learn thank you so much
Answer:
2p
Step-by-step explanation:
Take a trip back to simple division. What's 12/6? If you put 12 p's evenly into 6 piles, how many p's are in each pile?
2
Therefore, the answer is 2p.
What is the solution to 3 times the square root of 4 minus 2 times the square root of 4? A. 0 B. 1 C. 2 D. 3
For this case we have the expression:
"the square root of 4" is represented algebraically as:
[tex]\sqrt {4}[/tex]
Then, we can express the given statement as:
[tex]3 \sqrt {4} -2 \sqrt {4} =[/tex]
They are similar terms, we can subtract:
[tex]3 \sqrt {4} -2 \sqrt {4} = \sqrt {4} = \sqrt {2 ^ 2}[/tex]
By definition of power properties we have that:
[tex]\sqrt [n] {a ^ n} = a ^ {\frac {n} {n}} = a[/tex]
Then the expression is reduced to:
[tex]\sqrt {2 ^ 2} = 2[/tex]
Answer:
[tex]3 \sqrt {4} -2 \sqrt {4} = 2[/tex]
Use the parabola tool to graph the quadratic function
f(x)=(x−2)(x−6)
Graph the parabola by first plotting its vertex and then plotting a second point on the parabola.
Answer:
What parabola tool?
Step-by-step explanation:
I went ahead and graphed the quadratic function however, you should learn how to graph it yourself the way they are asking you to using the "parabola tool", because I cant really show you my steps in graphing it since I don't know what your parabola tool is.
Sorry
Write the slope-intercept form of the equation of each line.
Answer:
[tex]\large\boxed{y=-\dfrac{7}{3}x+4}[/tex]
Step-by-step explanation:
The slope-intercept form of an equation of a line:
[tex]y=mx+b[/tex]
m - slope
b - y-intercept (0, b)
The formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
We have the points:
(0, 4) → b = 4
and (3, -3)
Substitute:
[tex]m=\dfrac{-3-4}{3-0}=\dfrac{-7}{3}\\\\y=-\dfrac{7}{3}x+4[/tex]
Find the non permissible replacement for -5/3y
Answer:
0.
Step-by-step explanation:
The nonpermissible replacement of the variable in an expression is the value of x that will make the denominator of the expression zero.
This problem will therefore be written as -5/3y≠0, and it can't be 0, so 0 is your non permissible replacement.
Hope this helps!
How and why does 2x – 3 = -(3 – 2x )?
Answer:
Because the negative in the front cancels out the other neg.
Step-by-step explanation:
Answer:
-(3 - 2x ) = -3 + 2x = 2x - 3
Step-by-step explanation:
If you expand the brackets in -(3 - 2x) by multiplying all numbers by -1 (the negative symbol in front of the brackets represents negative 1 just without the 1)
Thus you get -3 + 2x.
Then rearranging the equation by swapping the 2x with the -3 you get 2x - 3.
Crystal earns $5.25 per hour mowing lawns. Write a rule to describe how the amount of money m earned is a function of the number of hours h spent mowing lawns. How much does Crystal earn if she works 2 hours and 15 minutes? m(h) = 5.25h; $11.29 ; $0.43 m(h) = 5.25h; $11.81 m(h) = 2h + 15; $25.50
Answer:
m(h) = 5.25h
$11.81 for 2 hours and 15 minutes
Step-by-step explanation:
Convert 2 hours and 15 minutes to an hour decimal: 2.25 hoursSubstitute 2.25 in for h.Multiply: (5.25)(2.25) = $11.81Drag the tiles to the correct boxes to complete the pairs. Not all tiles will be used.
Match each division expression with the correct quotient.
Answer:
[tex]\frac{16x^2+48x}{8x} = 2x+6\\\frac{56x^2-14x}{7x} = 8x-2\\\frac{18x^2+15x}{3x}=6x+5\\\frac{20x^2-32x}{4x}=5x-8[/tex]
Step-by-step explanation:
We will solve the division one by one:
[tex]\frac{16x^2+48x}{8x} = \frac{8x(2x+6)}{8x} = 2x+6\\\frac{56x^2-14x}{7x}=\frac{7x(8x+2)}{7x}=8x+2\\\frac{18x^2+15x}{3x} =\frac{3x(6x+5)}{3x} = 6x+5\\\frac{20x^2-32x}{4x}=\frac{4x(5x-8)}{4x}=5x-8[/tex]
a)
[tex]\dfrac{16x^2+48x}{8x}[/tex]
Since, both the terms in the numerator have a common factor as: 8x.
Hence, we take out common 8x from the numerator term and hence it could be written as:
[tex]\dfrac{8x(2x+6)}{8x}[/tex]
i.e.
[tex]=2x+6[/tex]
b)
[tex]\dfrac{56x^2-14x}{7x}[/tex]
Since, both the terms in the numerator have a common factor as: 14x.
Hence, we take out common 14x from the numerator term and hence it could be written as:
[tex]=\dfrac{14x(4x-1)}{7x}\\\\=2(4x-1)\\\\=8x-2[/tex]
c)
[tex]\dfrac{(18x^2+15x)}{3x}[/tex]
Since, both the terms in the numerator have a common factor as: 3x.
Hence, we take out common 3x from the numerator term and hence it could be written as:
[tex]=\dfrac{3x(6x+5)}{3x}\\\\=6x+5[/tex]
d)
[tex]\dfrac{20x^2-32x}{4x}[/tex]
Since, both the terms in the numerator have a common factor as: 4x.
Hence, we take out common 4x from the numerator term and hence it could be written as:
[tex]=\dfrac{4x(5x-8)}{4x}\\\\=5x-8[/tex]
Find the missing factor B that makes the equality true
42x^5y^4=(-7x^3y)(B)
Answer:
-6x^2 y^3 = B
Step-by-step explanation:
42x^5y^4=(-7x^3y)(B)
Solve for B
Divide by -7
42x^5y^4/-7=(-7x^3y)(B)/-7
-6 x^5 y^4 = x^3 y B
Divide by x^3
-6 x^5 y^4/x^3 = x^3 y B/x^3
-6 x^5/x^3 y^4 = By
-6 x^2 y^4
Divide by y
-6x^2 y^4/y = By/y
-6x^2 y^3 = B
Which graph shows all the values that satisfy 2/9 x+3 >4 5/9
Answer: A) 7 o---------------→
Step-by-step explanation:
[tex]\dfrac{2}{9}x+3>4\dfrac{5}{9}\\\\\\\text{Subtract 3 from both sides:}\\\\\dfrac{2}{9}x>1\dfrac{5}{9}\\\\\\\text{Convert the mixed number into an improper fraction:}\\\\\dfrac{2}{9}x>\dfrac{14}{9}\\\\\\\text{Multiply both sides by }\dfrac{9}{2}\text{ to isolate x:}\\\\x>\dfrac{14}{9}\times \dfrac{9}{2}\\\\\\\text{Simplify (cancel out the 9's and factor out a 2:}\\\\x>7[/tex]
The graph will have an open dot at 7 and the arrow will point to the right.
7 o--------->
Answer:
A
Step-by-step explanation:
EDGE 23
What is the equation of the line parallel to 3x+2y= -4 that goes through the point (4,-1)
Answer:
2y + 3x = 10
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
Rearrange 3x + 2y = - 4 into this form
Subtract 3x from both sides
2y = - 3x - 4 ( divide all terms by 2 )
y = - [tex]\frac{3}{2}[/tex] x - 2 ← in slope- intercept form
with slope m = - [tex]\frac{3}{2}[/tex]
• Parallel lines have equal slopes, thus
y = - [tex]\frac{3}{2}[/tex] x + c ← partial equation of parallel line
To find c substitute (4, - 1) into the partial equation
- 1 = - 6 + c ⇒ c = - 1 + 6 = 5
y = - [tex]\frac{3}{2}[/tex] x + 5 ← in slope- intercept form
Multiply through by 2
2y = - 3x + 10 ( add 3x to both sides )
3x + 2y = 10 ← in standard form
The equation of the line parallel to 3x+2y= -4 goes through the point (4,-1).
3x + 2y = 10 ← in standard form.y = - x + 5 ← in slope- intercept formEquation of lineThe general equation of a straight line exists y = mx + c, where m is the gradient, and y = c exists the value where the line cuts the y-axis. This number c is named the intercept on the y-axis. The equation of a straight line with gradient m and intercept c on the y-axis stands y = mx + c.
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
Rearrange 3x + 2y = - 4 into this form
Subtract 3x from both sides
2y = - 3x - 4 ( divide all terms by 2 )
y = - x - 2 ← in slope- intercept form
with slope m = -
• Parallel lines have equal slopes, thus
y = - x + c ← partial equation of parallel line
To find c substitute (4, - 1) into the partial equation
- 1 = - 6 + c ⇒ c = - 1 + 6 = 5
y = - x + 5 ← in slope- intercept form
Multiply through by 2
2y = - 3x + 10 ( add 3x to both sides )
3x + 2y = 10 ← in standard form.
To learn more about Equation of line refer to:
https://brainly.com/question/11552995
#SPJ2
Write an equation of the direct variation that includes the point (9, -12).
Answer:
[tex]y=-\frac{4}{3}x[/tex]
Step-by-step explanation:
we know that
A relationship between two variables, x, and y, represent a proportional variation if it can be expressed in the form [tex]y/x=k[/tex] or [tex]y=kx[/tex]
step 1
Find the value of k
we have
the point (9,-12)
x=9, y=-12
[tex]k=y/x[/tex]
substitute
[tex]k=-12/9=-4/3[/tex]
step 2
Find the equation
[tex]y=kx[/tex]
so
[tex]y=-\frac{4}{3}x[/tex]
the lines graphed below are parallel. the slope of the red line is -4/3. what is the slope of the green line
Answer:
-4/3
Step-by-step explanation:
If the lines are parallel, they have the same slope.
Since the red line has a slope of -4/3, the green line will have a slope of -4/3
What is the slope of the line passing through the points (1, 2) and (5, 4)?
Answer:
[tex]\frac{1}{2}[/tex] , or the first option
Step-by-step explanation:
The formula to find the slope of a line is [tex]\frac{y_{2} - y_{1}}{x_{2} - x_{1}}[/tex]. It doesn't matter which set of coordinates is (x₁,y₁), as long as you make sure you put them in the right places.
(x₁,y₁) = (1,2)
(x₂,y₂) = (5,4)
[tex]\frac{y_{2} - y_{1}}{x_{2} - x_{1}}[/tex] Plug in your numbers
[tex]\frac{4 - 2}{5 - 1}[/tex] Simplify
[tex]\frac{2}{4}[/tex] Simplify
[tex]\frac{1}{2}[/tex]
Answer:
slope = [tex]\frac{1}{2}[/tex]
Step-by-step explanation:
Calculate the slope m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (1, 2) and (x₂, y₂ ) = (5, 4)
m = [tex]\frac{4-2}{5-1}[/tex] = [tex]\frac{2}{4}[/tex] = [tex]\frac{1}{2}[/tex]
What are the answers plzzz someone help me
2. Find the products:
(1) (-2) * 3 * (-4)
(iv) 8 x 7*(-10)
Anyone please help . Who will answer Mark as the brainliest. Plzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzz help its urgent will be given 20 points
Answer:
24
-560
Step-by-step explanation:
(1) (-2) * 3 * (-4)
A negative time a negative is a positive
2*3*4 = 24
(iv) 8 x 7*(-10)
This result will be negative since there are positive times negative
8*7 =56* 10 = 560
8*7* (-10) = -560
Axis of symmetry of f(x)=(x+3)^2-8
ANSWER
[tex]x = - 3[/tex]
EXPLANATION
When a quadratic equation is in the vertex form,
[tex]f(x) = a {(x - h)}^{2} + k[/tex]
the equation of axis of symmetry is simply
[tex]x = h[/tex]
The given quadratic equation is
[tex]f(x) = {(x + 3)}^{2} - 8[/tex]
We can rewrite this as
[tex]f(x) = {(x - - 3)}^{2} - 8[/tex]
We now compare to
[tex]f(x) = a {(x - h)}^{2} + k[/tex]
We have
[tex]h = - 3 \: \: \: and \: \: k = - 8[/tex]
Therefore equation of axis of symmetry is:
[tex]x = - 3[/tex]
1. The price of a TV is $3,435. Which of
the following shows the values of the
two 3s in this price?
A 300; 3
B 30; 3
C 3,000; 3
D 3,000; 30
The correct option that shows the values of the two 3s in the price $3,435 is D) 3,000; 30
In the given price, $3,435, the first 3 represent the thousand place value, while the second 3 represents the one's place value.
The comma in option D indicates the separation of thousands, so it correctly represents the first 3 as part of the thousands place value.
The number 30 in option D represents the second 3 as part of the one's place value.
Therefore, option D) 3,000; 30 is the choice that correctly shows the values of the two 3s in the price $3,435.
Learn more about the number system here:
https://brainly.com/question/21751836
#SPJ2
Can you pls help me pls?
[tex]\dfrac{16}{7x+4}+A=\dfrac{49x^2}{7x+4}\\\\A=\dfrac{49x^2}{7x+4}-\dfrac{16}{7x+4}\\\\A=\dfrac{49x^2-16}{7x+4}\\\\A=\dfrac{(7x-4)(7x+4)}{7x+4}\\\\A=7x-4[/tex]
[tex]\bf \stackrel{~~~~~~~~\textit{is equivalent}}{\cfrac{16}{7x+4}+A~~=~~\cfrac{49x^2}{7x+4}}\implies \stackrel{\textit{cross-multiplying}}{\cfrac{16~~\begin{matrix} (7x+4) \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{~~\begin{matrix} 7x+4 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}+A(7x+4)=49x^2} \\\\\\ 16+A(7x+4)=49x^2\implies A(7x+4)=49x^2-16\implies A=\cfrac{49x^2-16}{7x+4}[/tex]
[tex]\bf A=\cfrac{7^2x^2-4^2}{7x+4}\implies A=\cfrac{\stackrel{\textit{difference of squares}}{(7x)^2-4^2}}{7x+4}\implies A=\cfrac{(7x-4)~~\begin{matrix} (7x+4) \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{~~\begin{matrix} 7x+4 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill A=7x-4~\hfill[/tex]
Create an equivalent system of equations using the sum of the system and the first equation.
−5x + 4y = 8
4x + y = 2
A) −5x + 4y = 8
9x + 5y = 10
B) −5x + 4y = 8
−x + 5y = 10
C) −5x + 4y = 8
9x + 5y = 2
D) −5x + 4y = 8
−x + y = 10
Answer:
B) {-5x + 4y = 8
{-x + 5y = 10
Step-by-step explanation:
Add like it said, and you will see your answer.
Answer:
Option B
[tex]-5x+4y=8[/tex]
[tex]-x+5y=10[/tex]
Step-by-step explanation:
We are given that
System of equations
[tex]-5x+4y=8[/tex]
[tex]4x+y=2[/tex]
We have to find an equivalent system of equations using sum of system and first equations
Sum of system of equations
[tex]-5x+4y+4x+y=8+2[/tex]
[tex]-x+5y=10[/tex]
Therefore, option B is true.
Write the expression -3x2 + 2y2 + 5xy - 2y + 5x2-3y2 in simplest form. Then, answer the following questions using
complete sentences.
a. How many terms are in the simplified expression?
b. How many of the terms in the simplified expression are negative?
WRITER
Answer: 2x^2-y^2+5xy-2y
a. There is four terms in the simplified expression.
b. Two terms in the simplified expression are negative.
Step-by-step explanation:
Write the expression like an addition/ subtraction problem.
-3x²+2y²+5xy-2y
+5x²-3y²
_________
This makes it easier to identify what to combine for like terms.
Final answer:
The simplified expression is 2x² - y² + 5xy - 2y. There are two negative terms in the simplified expression: -y² and -2y.
Explanation:
To simplify the expression -3x² + 2y² + 5xy - 2y + 5x² - 3y², we need to combine like terms. The like terms are the ones that contain the same variables to the same power. Here’s a step-by-step explanation:
Combine -3x² and +5x² to get +2x².Combine +2y² and -3y² to get -y².The terms +5xy and -2y do not have like terms, so they remain unchanged.The simplified expression is 2x² - y² + 5xy - 2y.
Now, to answer the question about the number of negative terms: in the simplified expression, there are two negative terms, which are -y² and -2y. A term is considered negative if it has a minus sign in front of it, indicating that it is less than zero when all other variables are considered to be positive.
A line intersects the point (-8,-1)and has a slope of 1/4.what is the slope-intercept equation for this line?
ANSWER
[tex]y = \frac{1}{4}x+1[/tex]
EXPLANATION
The slope-intercept equation of a straight line is of the form
[tex]y = mx + b[/tex]
Where 'm' is the slope and 'b' is the y-intercept.
From the question we have slope to be
[tex]m = \frac{1}{4} [/tex]
We substitute the slope into the slope-intercept equation and obtain:
[tex]y = \frac{1}{4}x + b[/tex]
To find the value of 'b' we plug in the point (-8,-1) into our current equation.
[tex] - 1= \frac{1}{4}( - 8)+ b[/tex]
[tex] - 1= - 2+ b[/tex]
[tex] - 1 + 2 = b[/tex]
[tex]1 = b[/tex]
[tex]b =1 [/tex]
The complete equation is
[tex]y = \frac{1}{4}x + 1[/tex]
Graph the system of equations to find the solutions of x3 + 6x2 - 40x = 192.
y = x3 + 6x2 - 40x
y = 192
Answer:
The solutions are: x=6. x=-4 and x=-8.
Step-by-step explanation:
The solution to the system of the equation is going to be given by the points where the graphs of:
y = x3 + 6x2 - 40x AND y = 192 intercept.
By looking at the graph, we can deduce they intercept at three points:
(-8, 192), (-4, 192) and (6, 192).
Another way to verify this, is by solving the following system of equations:
x3 + 6x2 - 40x - 192 = 0
Factorizing, we get:
(x-6)(x+4)(x+8) = 0
Where we can clearly see that the solutions are: x=6. x=-4 and x=-8.
Answer:
A -8
B -4
D 6
Step-by-step explanation:
Correct on EDGE
Explain why there can be no infinite geometric series with a first term of 12 and a sum of 5.
Answer:
Step-by-step explanation:
When you find the sum of a number you are adding two or more numbers together. therefore the only answer that you could use to get a sum of 5 when your first term is 12 would be -7
Please help Geometry
Answer:
Volume = 784*pi
Step-by-step explanation:
We are given the height and radius of cylinder
So,
Radius = r = 7
Height = h = 16
The formula for finding volume of cylinder is:
[tex]Volume=\pi r^{2} h\\Putting\ in\ the\ values\ of\ r\ and\ h\\Volume=\pi *(7)^{2}*16\\V=\pi *49*16\\V=784\pi [/tex]
Answer:
Volume of cylinder = 784 cubic units
Step-by-step explanation:
Points to remember
Volume of cylinder = πr²h
Where r - Radius of cylinder and
h - Height of cylinder
To find the volume of cylinder
It is given that,
radius r = 7 units and height h = 16 units
Volume of cylinder = πr²h
= π * 7² * 16
= 784 cubic units
Therefore Volume of cylinder = 784 cubic units